Prevalence, antibiotic susceptibility, and genomic analysis of Vibrio alginolyticus isolated from seafood and freshwater products in China - Sun, Yanan; Yan, Yanfei; Yan, Shaofei; Li, Fengqin; Li, Ying; Yan, Lin; Yang, Dajin; Peng, Zixin; Yang, Baowei; Sun, Jiali; Xu, Jin; Dong, Yinping; et al. (Frontiers in Microbiology, 2024)
This study characterized Vibrio alginolyticus isolated from sea food and freshwater products in China (2020). 122 (95.31%) V. alginolyticus isolates were resistant to at least one category of antibiotic and 2 (1.56%) isolates were resistant to at least three antibiotic categories and belong to multi-drug resistance (MDR) isolates.High prevalence rate was observed to be blaCARB (98.04 %) that encoding beta-lactam resistance, followed by tet (97.06%) encoding tetracycline resistance and fos (4.90%) encoding resistance to fosfomycin. Among the 57 V. alginolyticus isolates, the commonest virulence genes were type III secretion system translocated gene vopD, vopB and vcrH (54.4%, 31/57), type III secretion system regulated gene tyeA (54.39%), followed by vscI and vscF (50.88%) encoded type III secretion system inner rod protein and needle protein, respectively. Multi-locus sequence typing (MLST) revealed considerable genetic diversity, with 34 distinct sequence types (STs) identified among 55 isolates. ST421 (n=5), ST166 (n=4), ST523 (n=3), ST516 (n=3) and ST507 (n=3) were dominant STs among 55 V. alginolyticus isolates. These findings highlight the widespread occurrence of V. alginolyticus in both freshwater and seafood products, underscoring the critical need for vigilant monitoring of these bacteria. Such measures are essential for ensuring effective food safety management and safeguarding public health.